2021
DOI: 10.1111/ajt.16428
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcome of SARS-CoV-2 infection on solid organ transplantation recipients: A nationwide population-based study

Abstract: Since February 21 2020, when the Italian National Institute of Health (Istituto Superiore di Sanità–ISS) reported the first autochthonous case of infection, a dedicated surveillance system for SARS‐CoV‐2‐positive (COVID+) cases has been created in Italy. These data were cross‐referenced with those inside the Information Transplant System in order to assess the cumulative incidence (CI) and the outcome of SARS‐COV‐2 infection in solid organ transplant recipients (SOTRs) who are assumed to be most at risk. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
114
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(129 citation statements)
references
References 29 publications
7
114
6
Order By: Relevance
“…The nationwide study from the Italian registry reported that the cumulative incidence of COVID infection in SOT recipients was 1.02%, which was significantly higher than the non-transplant patients (0.4%) (p < 0.05) [51]. Among 450 SOT recipients with SAR-CoV-2 infection, 89 (19.8%) were LT recipients).…”
Section: Sars-cov-2 Infection In Liver Transplant Recipientsmentioning
confidence: 96%
See 1 more Smart Citation
“…The nationwide study from the Italian registry reported that the cumulative incidence of COVID infection in SOT recipients was 1.02%, which was significantly higher than the non-transplant patients (0.4%) (p < 0.05) [51]. Among 450 SOT recipients with SAR-CoV-2 infection, 89 (19.8%) were LT recipients).…”
Section: Sars-cov-2 Infection In Liver Transplant Recipientsmentioning
confidence: 96%
“…Out of 450 patients, 123 patients died during the follow-up period. The 30-day and 60-day mortality rates were lower in LT recipients compared to heart and kidney recipients (Table 3) [51].…”
Section: Sars-cov-2 Infection In Liver Transplant Recipientsmentioning
confidence: 97%
“…A nationwide population study in Italy found that the cumulative incidence of SARS-CoV-2 infection was higher in transplant recipients than in patients who had not had a transplant. 6 When stratified by type of organ transplant, the cumulative incidence was higher for heart transplants and lower for liver transplants versus kidney transplants. 6 However, more organ transplant recipients had two or three comorbidities than did the control population.…”
Section: Implications Of Covid-19 For Patients With Pre-existing Digementioning
confidence: 99%
“…6 When stratified by type of organ transplant, the cumulative incidence was higher for heart transplants and lower for liver transplants versus kidney transplants. 6 However, more organ transplant recipients had two or three comorbidities than did the control population. 6 An analysis of 151 liver transplant recipients with SARS-CoV-2 infection in the COVID-Hep and SECURE-Cirrhosis registries showed that liver transplantation was not independently associated with death, whereas known risk factors, such as increased age and presence of comorbidities were.…”
Section: Implications Of Covid-19 For Patients With Pre-existing Digementioning
confidence: 99%
See 1 more Smart Citation